Theoretical modeling and experimental validation of laser-generated focused ultrasound and micro-cavitation dynamics - Min Gyu Joo; Jeongmin Heo; Ki Joo Pahk; Hyoung Won Baac (Ultrasonics Sonochemistry, 2025)
This study presents a fully coupled numerical simulation method for modeling the behavior of laser-generated focused ultrasound (LGFU) in complex structures, including in vivo environments. Using finite element method (FEM) simulations, we achieve peak pressures of 241 MPa and 34.7 MPa in the positive and negative phases, respectively, of the LGFU waveform. The use of adaptive mesh refinement (AMR) enables us to perform tight mesh simulations with a size of 0.06 μm and calculate ultrafast rise time (0.8 ns) of the LGFU wavefront. We also propose an improved LGFU-induced bubble model that can simulate nano-sized seed bubbles, which is achieved by combining the Gilmore equation with heat and mass transfer and modified Young-Laplace (MY-L) equations. We demonstrate the effectiveness of the model by validating it against experimental results in water, where we achieve a 29.6 % improvement in maximum bubble size and a 34.5 % improvement in bubble lifetime compared to the previous model. Furthermore, we apply the model to a tissue mimicking phantom and obtain results that are consistent with experimental observations. Our proposed simulation method provides a powerful tool for investigating LGFU-induced bubble behavior in complex structures, which could have important applications in fields such as biomedical engineering.© 2017 Elsevier Inc. All rights reserved.